2020
DOI: 10.1002/slct.201904059
|View full text |Cite
|
Sign up to set email alerts
|

Amino‐Acid‐Mediated Aerobic Oxidation of Organoborons for the Synthesis of Phenolic Derivatives Using Single Electron Transfer

Abstract: An efficient amino‐acid‐mediated ipso‐hydroxylation of arylboronic acids, aryl boronate esters and aryl trifluoroborates to aryl alcohols has been described. The current protocol was realized by using sub‐stoichiometric amount of l‐histidine in presence of triethylamine under aerobic conditions in DMF as solvent. This amino‐acid‐mediated process provides an alternative route for the hydroxylation of organoborons through in situ generation of hydrogen peroxide. The present protocol explores the synthetic utilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…In most cases, literature reports reveal the requirement for a base/metal in the reaction when phenylboronic acid reacts with reactive oxygen species. 22 The mechanism of the reaction is ambiguous, particularly in light of the fact that the reaction can occur in the absence of any base/metal under air. Via control experiments, we have already confirmed that a radical process might be involved in the transformation.…”
Section: Resultsmentioning
confidence: 99%
“…In most cases, literature reports reveal the requirement for a base/metal in the reaction when phenylboronic acid reacts with reactive oxygen species. 22 The mechanism of the reaction is ambiguous, particularly in light of the fact that the reaction can occur in the absence of any base/metal under air. Via control experiments, we have already confirmed that a radical process might be involved in the transformation.…”
Section: Resultsmentioning
confidence: 99%
“…An ortho-substituted phenol 9 was obtained as a result of amino acid mediated aerobic oxidation of the corresponding boronic ester 8h. 12 In conclusion, we have reported the utilization of anion−π interactions between carbonate anions and easily accessible aryl halides for the synthesis of aryl phosphonates and aryl boronates. The photoinduced C−X activation pathway operates via a radical mechanism initiated by an intrasystem SET.…”
mentioning
confidence: 88%
“…Similarly, with a phenyl substituent, 43% of the desired product was obtained (when X = Br) that increased to 65% in the case of the iodo substituent (Scheme , product 8g ). An ortho -substituted phenol 9 was obtained as a result of amino acid mediated aerobic oxidation of the corresponding boronic ester 8h …”
mentioning
confidence: 99%